Selected Parameters of Huacaya Alpacas Fibers and Olkuska Sheep Wool - Katarzyna Czyż; Anna Wyrostek; Jakub Smoliński; Natalia Kondracka; Maria Pietrzyńska (Journal of Natural Fibers)
Although fibers of animal origin make up only a small part of the global textile fiber industry, sheep’s wool and also fibers of other species like alpaca, due to their unique properties, are an important and appreciated part of this industry. Our study involves the analysis of mechanical and physical properties of fibers derived from Huacaya alpacas and Olkuska sheep. Additionally, the wool of Olkuska sheep lambs was also analyzed. Fibers belonging to ten individuals of each species were evaluated for their diameter, breaking force, elongation at break, tenacity and heat transfer rate. It was found that the diameter of alpaca fibers was lower than that of sheep fibers, while the fibers of lambs were thinnest. A dependence was observed between the breaking force and fiber diameter. The stress parameter analogically to breaking elongation showed significant and highly significant differences for analyzed fibers. The highest values were shown for sheep, followed by alpaca and lamb. The heat transfer rate was the highest in alpacas. The study demonstrated that fibers from both alpacas and sheep are suitable for yarn material.